Eat your peas, Louise! - Snow, Pegeen; Venezia, Mike (New York : Scholastic, 1985)
Illustrations and simple text tell a story about Louise and all the reasons she is given for eating her peas.
"Early fluent, level B"--Cover p. [4].
"Prepared under the direction of Robert Hillerich.".
1.
1.4
K-3
P-2.
Keywords: Food -- Fiction; Peas -- Fiction; Stories in rhyme; Food -- Fiction; Peas -- Fiction; Stories in rhyme; Readers (Elementary).